THE IMPACT OF EDUCATION, TEAMWORK, AND COMMUNICATION ON EMPLOYEE PERFORMANCE AT THE WOMEN'S EMPOWERMENT AND CHILD PROTECTION OFFICE OF THE RIAU ISLANDS PROVINCE THROUGH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Eva Agustina; Ngaliman; Ana Faizah (CV. Radja Publika, 2025)
This study analyzes the influence of education, teamwork, and communication on the performance of employees at the Department of Women’s Empowerment and Child Protection of Riau Islands Province, with organizational commitment as an intervening variable. The high number of cases of violence against women and children from 2020 to 2024 presents a serious challenge for government institutions in effectively carrying out their main duties and functions. This research employs a quantitative approach, using survey methods for data collection. Questionnaires were distributed to 105 employees of the Department of Women’s Empowerment and Child Protection of Riau Islands Province.The results indicate that improving education and strengthening teamwork have a significant direct effect on employee performance and organizational commitment. In contrast, communication does not significantly influence performance or organizational commitment. Moreover, the indirect effect of communication on performance through organizational commitment was also found to be insignificant. Based on these findings, it is recommended that efforts be focused on improving digital communication skills among employees, as well as other factors that have a stronger direct impact on enhancing employee performance at the Department of Women’s Empowerment and Child Protection, Population Control, and Family Planning of the Riau Islands Province.